The Improvement of Students' Speaking Skill Through Storytelling - Marsevani, Maya; Rahman, Diana Merliana (Lingual Journal of Language and Culture, 2022)
This research was conducted in an Islamic private junior high school in Batam and was conducted on 7th grade students with a total of 10 students. This research includes Classroom Action Research (CAR). Started with the problem faced the student such as lack of vocabulary, lack the proper motivation to study and practice speaking, not confident to speak. Responding to the problems, the right method of learning to speak English should be how to train memory, pronunciation, and hearing simultaneously, namely storytelling. Before the storytelling method was applied, students were given a pre-test to get the average grade for the class. After that, the average value of the class that has been obtained will be measured by the rubric. The total students’ average was 2.2 (poor). After looking at the results of the pre-test, researchers saw that with practice conversation, speaking skills of students can’t develop well. Because of that in the treatment 1, application cycle 1 and also post-test. The post-test results were 2.76. It can be said that the storytelling can help develop students' speaking abilities to improve.